The paradox of vaginal examination practice during normal childbirth: Palestinian women's feelings, opinions, knowledge and experiences - Hassan Sahar J; Sundby Johanne; Husseini Abdullatif; Bjertness Espen (BMC, 2012)
Abstract Background Vaginal examination (VE), is a frequent procedure during childbirth. It is the most accepted ways to assess progress during childbirth, but its repetition at short intervals has no value. Over years, VE continued to be plagued by a nature that implies negative feelings and experiences of women. The aim of this exploratory qualitative study was to explore women's feelings, opinions, knowledge and experiences of vaginal examinations (VE) during normal childbirth. Methods We interviewed 176 postpartum women using semi-structured questionnaire in a Palestinian public hospital in the oPt. Descriptive statistics were conducted; frequency counts and percentages for the quantitative questions. The association between the frequency of VE and age, parity, years of education, locale and the time of delivery was tested by Chi-squared and Fisher's Exact test. The open-ended qualitative questions were read line-by-line for the content and coded. The assigned codes for all responses were entered to the SPSS statistical software version 18. Results As compared with WHO recommendations, VE was conducted too frequently, and by too many providers during childbirth. The proportion of women who received a 'too high' frequency of VEs during childbirth was significantly larger in primipara as compared to multipara women (P = .037). 82% of women reported pain or severe pain and 68% reported discomfort during VE. Some women reported insensitive approaches of providers, insufficient means of privacy and no respect of dignity or humanity during the exam. Conclusions Palestinian women are undergoing unnecessary and frequent VEs during childbirth, conducted by several different providers and suffer pain and discomfort un-necessarily. Practice implications Adhering to best evidence, VE during childbirth should be conducted only when necessary, and if possible, by the same provider. This will decrease the laboring women's unnecessary suffering from pain and discomfort. Providers should advocate for women's right to information, respect, dignity and privacy.